NODULAR MALIGNANT MELANOMA - OR MAYBE NOT? - Cabral, Rita (2014)
Eccrine poroma is a relatively rare benign adnexal tumor with multiple clinical presentations, mimicking several other cutaneous neoplasms. The pigmented form is uncommon and usually located in nonacral sites in non-white patients. The authors present the case of a patient with a pigmented tumoural lesion on the left shoulder clinically thought to represent nodular malignant melanoma, but whose histopathology revealed a pigmented form of eccrine poroma. The lesion was surgically removed and no recurrence was seen after six months of follow-up.